Effectiveness of Motor Imagery Training on Improving Upper Extremity Functional Ability Post Stroke: A Systematic Review - Isa Taufiq; Sri Sulistiyawati; Yurike Septianingrum; Siti Nur Hasina (Indonesian Journal of Global Health Research, 2025)
Increasingly acknowledged for its ability to improve motor function and neuroplasticity in stroke therapy is motor imagery (MI) training. Variability in techniques and results, however, calls for a methodical assessment to combine the data. Objective: The goal of this study was to assess whether MI training will help stroke patients achieve better motor performance and other rehabilitation results. Method: After a thorough search across five databases using PubMed, Scopus, Google Scholar, Web of Science, and Cochrane Library in line with PRISMA criteria, we took ten works published between 2023 and 2025 under consideration. Resulting in 578 entries and Ultimately 10 studies were included in the review. methodological quality was assessed using JBI critical assessment techniques. Result:Ten research were examined and MI-based therapies clearly improved upper limb function, neuroplasticity, and attentional control. MI with BCI showed improved cortical activation, brain connection, and muscular strength. In severe cases especially, MI combined with TMS enhanced motor recovery. Furthermore, MI training enhanced with virtual reality or voice direction improved psychological well-being and daily life activities. Conclusion: MI-based treatments—especially in conjunction with cutting-edge technologies—effectively enhance motor and cognitive performance in stroke victims. To maximise clinical use, future studies should standardise procedures, investigate reasonably priced delivery strategies, and evaluate long-term advantages.